State Responsibility for Climate-Harmful Development: China's Governance Gap in Coal Policy Implementation - Yordan Gunawan; Safira Ayu Tri Ariyani; M. Fabian Akbar; Manuel Beltrán Genovés (Fakultas Hukum Universitas Lampung, 2026)
China's continued expansion of coal projects has intensified tensions between national development priorities and international climate commitments. Although China has pledged to mitigate climate change under the UNFCCC and the Paris Agreement, the persistence of coal-based development raises important questions regarding the implementation of these commitments through domestic governance. This study examines China's coal policy from the perspective of state responsibility under international environmental law, focusing on the principles of no-harm, due diligence, precaution, and the normative framework of the Paris Agreement. Using a normative legal research approach, the study analyzes the relationship between international legal obligations and domestic policy implementation. The findings show that the principal challenge lies not in the absence of international legal standards but in the governance gap between central climate commitments and provincial implementation of coal policies, resulting in inconsistent enforcement of environmental obligations.